Self concept and job satisfaction of office information managers in private universities in Ibadan, Oyo State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The interplay between self-concept and job satisfaction among office information managers warrants significant attention due to its potential implications for individual well-being and organizational effectiveness. This study, examined the influence of self-concept on job satisfaction of office information managers in Private Universities, Ibadan, Oyo State. The study is a survey. The populations consist of 130 office information managers from six private universities in Ibadan. Total enumeration was used to sample all the 130 respondents. Data was collected using questionnaire. The data collected was analyzed using both descriptive and inferential statistics. The study found a very high job satisfaction level (Mean=3.9) and amoderate self-concept (Mean=2.7) among respondents. The test of hypothesis showed that self-concept has no significant influence on job satisfaction (Adj.R2= 0.026, F(1,103)=2.699, p=.103b). The study concluded that by shedding light on these dynamics, this article provides valuable insights for organizational leaders, human resource practitioners, and office information managers themselves, enabling them to leverage self-concept principles to cultivate a fulfilling and rewarding work experience. It therefore recommends Universities should encourage self-awareness and self-development among office information managers. Providing opportunities for personal and professional growth, mentorship programs, and self-confidence-building initiatives can help strengthen their self-concept.